Pole piece and preparation method thereof, solid-state battery and power utilization device

By using the interference matching technology of porous solid electrolyte membrane and active material particles in the pole sheet of the solid-state battery, the problems of low bonding strength and high impedance of the solid-state battery interface are solved, and higher battery performance and lower active material inactivation rate are achieved.

CN119890223APending Publication Date: 2025-04-25REPT BATTERO ENERGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510079903.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Solid-state batteries have problems with low interface bonding strength and high impedance, which affects the cycling and rate performance of the battery. At the same time, it is impossible to realize all-solid-state batteries. In addition, traditional methods are prone to agglomeration and inactivation of active material particles during the preparation of the electrode sheet.

Method used

A porous solid electrolyte membrane is used as the electrode sheet material. A plurality of discrete pores are provided in the membrane, and active material particles are embedded in the pores. At least some of the active material particles are interspersed with the pores through spraying and rolling processes to improve bonding strength and reduce impedance.

Benefits of technology

The lithium conduction capability at the polar sheet level is improved, the interface bonding strength is enhanced, the impedance is reduced, the cycle performance, rate performance and capacity performance of solid-state batteries are improved, and the agglomeration and inactivation of active material particles is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890223A_ABST
    Figure CN119890223A_ABST
Patent Text Reader

Abstract

The invention relates to a pole piece and a preparation method thereof, a solid-state battery and an electric device. The pole piece comprises a porous solid electrolyte membrane, the porous solid electrolyte membrane is provided with a plurality of discrete pore channels, active material particles are arranged in the pore channels, and at least part of the active material particles are in interference fit with the pore channels. According to the pole piece provided by the invention, on one hand, the active material particles in the pore channels of the porous solid electrolyte membrane are in interference fit with the pore channels, so that the bonding strength between the active material particles and the porous solid electrolyte membrane can be improved, the interface impedance is reduced, and the rate capability and the cycle performance of the battery are improved; and on the other hand, the pore channels of the porous solid electrolyte membrane are separated from each other, so that compared with mutually communicated pore channels in the traditional technology, the accumulation of active material particles can be prevented, the probability of inactivation of the active material particles is reduced, and the capacity performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a pole piece and a preparation method thereof, a solid-state battery, and an electrical device. Background Art

[0002] Compared with liquid batteries, solid-state batteries use solid electrolytes and are less prone to combustion and explosion, so they have higher reliability.

[0003] However, current solid-state batteries have problems with low interface bonding strength and high impedance, which affect the battery's cycle performance and rate performance. In addition, for the positive and negative electrode layers of solid-state batteries, since they cannot be coated on the surface of the active material, lithium conduction at the electrode layer cannot be achieved, and the electrolyte still needs to be filled into the electrode pores. Therefore, solid-state batteries cannot truly achieve full solid-state. In addition, the industry uses methods such as templates to solve the lithium conduction problem at the electrode layer of all-solid-state batteries, but this method is prone to the problem of active material particles agglomerating and deactivating during the preparation of the electrode, which affects the battery's capacity performance. Summary of the invention

[0004] Based on this, it is necessary to provide a pole piece and its preparation method, a solid-state battery, and an electrical device to improve the interface bonding strength of the solid-state battery, reduce impedance, reduce the agglomeration of active material particles, and improve the cycle performance, rate performance, and capacity performance of the solid-state battery.

[0005] The first aspect of the present application provides a pole piece, which includes: a porous solid electrolyte membrane having a plurality of discrete pores, wherein active material particles are arranged in the pores, and at least some of the active material particles are interference fit with the pores.

[0006] In some embodiments, the circumference C of the pores and the maximum particle size d of the active material particles satisfy: 1 / 3πd <C<πd。

[0007] In some embodiments, the center distance L between two adjacent channels and the maximum particle size d of the active material particles satisfy: 1.1d <L<10d。

[0008] In some embodiments, the depth D of the pores and the maximum particle size d of the active material particles satisfy: D>1.05d.

[0009] In some embodiments, the solid electrolyte in the porous solid electrolyte membrane is an organic solid electrolyte.

[0010] The second aspect of the present application provides a method for preparing an electrode sheet, which comprises the following steps: spraying active material particles on a porous solid electrolyte membrane, and then rolling it so that at least part of the active material particles are interference fit with the pores of the porous solid electrolyte membrane; wherein the pores of the porous solid electrolyte membrane are arranged discretely from each other.

[0011] In some embodiments, the number of rolling steps is greater than or equal to two times.

[0012] In some embodiments, the method further comprises the following steps before rolling: ultrasonicating and rearranging the active material particles.

[0013] The third aspect of the present application provides a solid-state battery, which includes: two pole pieces provided in the first aspect or pole pieces prepared by the preparation method provided in the second aspect, the active material particles are positive electrode active material particles or negative electrode active material particles, one pole piece is positive electrode active material particles, and the other pole piece is negative electrode active material particles; and a dense solid electrolyte membrane, which is arranged between the two pole pieces.

[0014] A fourth aspect of the present application provides an electrical device, which includes the solid-state battery provided by the third aspect.

[0015] Compared with the traditional technology, this application has at least the following beneficial effects:

[0016] The electrode provided in the present application, on the one hand, can improve the bonding strength between the active material particles and the porous solid electrolyte membrane by the interference fit between the active material particles in the pores of the porous solid electrolyte membrane and the pores, reduce the interface impedance, and improve the rate performance and cycle performance of the battery; on the other hand, the pores of the porous solid electrolyte membrane are separated from each other, and compared with the pores that penetrate each other in traditional technologies, the accumulation of active material particles can be prevented, the probability of inactivation of active material particles is reduced, and the capacity performance of the battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram showing the comparison of active material particles before and after being pressed onto a porous solid electrolyte membrane in one embodiment of the present application.

[0018] Figure 2 Schematic diagram of the relationship between the distances between two adjacent pores of a porous solid electrolyte membrane in one embodiment of the present application.

[0019] Figure 3 It is a schematic diagram of the structure of a pole piece preparation device in one embodiment of the present application.

[0020] Reference numerals:

[0021] 1. Pole piece; 11. Porous solid electrolyte membrane; 110. Pores; 12. Active material particles; 2. Pole piece preparation device; 21. Laser puncher; 22. Main material powder disperser; 23. Roller pressing device; 24. Ultrasonic homogenizer; 25. Intercepting homogenizer; 26. Micro-negative pressure powder absorber. DETAILED DESCRIPTION

[0022] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0023] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0024] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0025] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0026] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0027] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0028] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0029] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0030] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0031] The first aspect of the present application provides a pole piece 1, such as Figure 1 and Figure 2 As shown, the pole piece 1 comprises a porous solid electrolyte membrane 11. The porous solid electrolyte membrane 11 has a plurality of discrete channels 110, in which active material particles 12 are arranged, and at least part of the active material particles 12 are interference fit with the channels 110.

[0032] The electrode 1 provided in the present application, on the one hand, can improve the bonding strength between the active material particles 12 and the porous solid electrolyte membrane 11 through the interference fit between the active material particles 12 in the pores 110 of the porous solid electrolyte membrane 11, reduce the interface impedance, and improve the rate performance and cycle performance of the battery; on the other hand, the pores 110 of the porous solid electrolyte membrane 11 are separated from each other, compared with the pores 110 that penetrate each other in the traditional technology, it can prevent the accumulation of active material particles 12, reduce the probability of inactivation of the active material particles 12, and improve the capacity performance of the battery.

[0033] Herein, the role of the “porous solid electrolyte membrane 11 ” is to serve as a carrier for accommodating the active material particles 12 , while increasing the interface contact area, thereby reducing the interface impedance.

[0034] In this text, "interference fit" means that the elastic property of the active material particles 12 is utilized to make the active material particles 12 fit tightly with the pore channels 110, so that the active material particles 12 are tightly embedded into the pore channels 110 of the porous solid electrolyte membrane 11.

[0035] In some embodiments, the perimeter C of the pore channels 110 and the maximum particle size d of the active material particles 12 satisfy: 1 / 3πd < C < πd. When the perimeter C of the pore channels 110 is within the above range, it can not only make the active material particles 12 have an interference fit with the pore channels 110, improve the bonding strength between the active material particles 12 and the porous solid electrolyte membrane 11, reduce the interfacial impedance, improve the rate performance and cycling performance of the battery, but also prevent the porous solid electrolyte membrane 11 from being broken during the process of pressing in the active material particles 12, reduce the phenomenon of tape breakage, and improve the process yield.

[0036] In this text, the "perimeter of the pore channels 110" refers to the sum of the lengths of the closed figures formed by the pore channels 110 on the surface of the porous solid electrolyte membrane 11.

[0037] This application does not limit the shape of the closed figure formed by the pore channels 110 on the surface of the porous solid electrolyte membrane 11. Specifically, when the closed figure is a slit or a long strip, since its width can be ignored, the perimeter C of the pore channels 110 is twice the length of the slit; when the closed figure is a circle, the perimeter C of the pore channels 110 is the diameter of the pore channels 110 * π.

[0038] In this text, the "maximum particle size of the active material particles 12" refers to the maximum size of the active material particles 12 in three-dimensional space, which can be measured by a laser particle size analyzer.

[0039] In some embodiments, when the active material particles 12 are spherical particles, the maximum particle size d of the active material particles 12 is the diameter of the spherical particles.

[0040] In some embodiments, when the maximum particle size d of the active material particles 12 is in the range of x to y, the perimeter C of the pore channels 110 x-y satisfies: 1 / 3πy < C x-y < πx, where 1 / 3y < x < y. When the maximum particle size d of the active material particles 12 is in the range of x to y and 1 / 3y < x < y, in order to achieve an interference fit while ensuring the stability of the porous solid electrolyte membrane 11, the perimeter C of the pore channels 110 needs to satisfy both conditions of 1 / 3πx < C < πx and 1 / 3πy < C < πy, and taking the intersection gives 1 / 3πy < C x-y<πx. Thus, the active material particles 12 can be screened into multiple types of active material particles 12 according to the above conditions, and corresponding types of pores 110 are formed on the solid electrolyte membrane for matching, reducing the agglomeration of the active material particles 12 and lowering the impedance of the electrode sheet 1.

[0041] In some embodiments, the center distance L between two adjacent pores satisfies: 1.1d < L < 10d with respect to the maximum particle size d of the active material particles. Thus, on the one hand, by defining L > 1.1d, it can be ensured that the pores 110 of the porous solid electrolyte membrane 11 are discretely arranged from each other, and it can also prevent the porous solid electrolyte membrane 11 from being broken during the process of pressing the active material particles 12, reducing the phenomenon of tape breakage and improving the process yield. On the other hand, by defining L < 10d, it can prevent the reduction of the battery energy density caused by the overly sparse distribution of the active material particles 12.

[0042] In this article, the "center distance L between the pores" refers to the center linear distance of the closed figure formed by the adjacent pores 110 of the porous solid electrolyte membrane 11 on the surface of the porous solid electrolyte membrane 11 before the active material particles 12 are embedded.

[0043] In some embodiments, the depth D of the pores 110 satisfies: D > 1.05d with respect to the maximum particle size d of the active material particles 12. During the process of pressing the active material particles 12 into the pores 110, the active material particles 12 will be compressed (the maximum compression is about 5% of their particle size). Therefore, within the above range of the depth D of the pores 110, it can reserve space for the compression of the porous solid electrolyte membrane 11 and prevent the active material particles 12 from coming out.

[0044] In some embodiments, the solid electrolyte in the porous solid electrolyte membrane 11 is an organic solid electrolyte. Since the organic solid electrolyte has flexibility and processability, forming pores on the film layer made of the organic solid electrolyte can prevent the electrode sheet 1 from cracking and improve the process yield.

[0045] In some embodiments, the organic solid electrolyte is selected from one or more of the following: polyacrylonitrile (PAN), polyethylene oxide (PEO), polysiloxane (PSO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride - hexafluoropropylene (PVDF - HFP), polymethyl methacrylate (PMMA), and their derivatives.

[0046] In the traditional technology, the structure of the electrode prepared by the dry process is a current collector and a film layer formed by roll - pressing a mixture of active material particles, conductive agents, and binders on the surface of the current collector. However, this method is prone to cause tape breakage, resulting in a decrease in the yield, and it is also difficult to solve the contact problem between the film layer and the current collector.

[0047] In some embodiments, the porous solid electrolyte membrane 11 further includes a conductive agent. By adding a conductive agent to the porous solid electrolyte membrane 11, the porous solid electrolyte membrane 11 can not only use the solid electrolyte material therein to transmit ions in the active material particles 12, but also act as a conductive current collector, which simplifies the structure of the pole piece 1 and can adjust the film thickness of the pole piece 1, thereby avoiding the contact problem between the membrane layer and the current collector in the electrode prepared by the traditional dry process.

[0048] The conductive agent may be any conductive agent commonly used in the art. In some embodiments, the conductive agent is selected from one or more of conductive carbon black, acetylene black, graphene and carbon nanotubes.

[0049] In some embodiments, the porous solid electrolyte membrane 11 further includes a binder.

[0050] The binder may be any commonly used binder in the art. In some embodiments, the binder is selected from one or more of styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC) and polyvinylidene fluoride (PVDF).

[0051] In some embodiments, the porous solid electrolyte membrane 11 further includes an electrolyte salt.

[0052] In some embodiments of the present application, the electrolyte salt is a lithium salt, and the lithium salt includes at least one of an inorganic lithium salt and an organic lithium salt. The inorganic lithium salt includes at least one of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4) and lithium hexafluorophosphate (LiPF6). The organic lithium salt includes at least one of lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0053] In some embodiments of the present application, the mass ratio of the solid electrolyte, the conductive agent, the binder and the electrolyte salt in the porous solid electrolyte membrane 11 is (1-10): (1-5): (1-2): (1-5); preferably (2-5): 3:1:3.

[0054] A second aspect of the present application provides a method for preparing a pole piece 1, the method comprising the following steps:

[0055] Active material particles 12 are sprayed on the porous solid electrolyte membrane 11 and then rolled, so that at least part of the active material particles 12 are interference-fitted with the pores 110 of the porous solid electrolyte membrane 11 .

[0056] The pores 110 of the porous solid electrolyte membrane 11 are arranged separately from each other.

[0057] The preparation method of the electrode 1 provided in the present application forms an interference fit between at least part of the active material particles 12 and the pores 110 by spraying active material particles 12 on the porous solid electrolyte membrane 11 and then performing a rolling process, thereby improving the bonding strength between the active material particles 12 and the porous solid electrolyte membrane 11, reducing the interface impedance, and improving the rate performance and cycle stability of the battery; the pores 110 of the porous solid electrolyte membrane 11 are arranged separately from each other, so that the active material particles 12 can be dispersed into independent pores 110 during the spraying and rolling process. Compared with the pores 110 that are interconnected in the traditional technology, the accumulation of active material particles 12 can be prevented, the probability of inactivation of active material particles 12 is reduced, and the capacity performance of the battery is improved; the above-mentioned preparation method adopts the process steps of spraying and rolling, which is simple to operate, highly controllable, and suitable for industrial production.

[0058] In addition, the method for preparing the pole piece 1 does not require the use of additional organic solvents, thereby reducing the manufacturing cost of the battery cell and improving the environmental friendliness during the production process.

[0059] In some embodiments, the number of rolling is greater than or equal to two times. Since the active material particles 12 need to have an interference fit with the pores 110, rolling greater than or equal to two times is conducive to pressing the active material particles 12 into the pores 110, improving the bonding strength between the active material particles 12 and the pores 110, further improving the coating effect of the porous solid electrolyte membrane 11, reducing the interface impedance, and improving the rate performance and cycle performance of the battery.

[0060] In some embodiments, before rolling, the following steps are further included: ultrasonicating and rearranging the active material particles 12 so that the active material particles 12 can enter the pores 110 as much as possible.

[0061] In some embodiments, the pores 110 of the porous solid electrolyte membrane 11 are formed by laser drilling, cutting or metal stamping.

[0062] In some embodiments, before spraying the active material particles 12 on the porous solid electrolyte membrane 11, the following steps are included:

[0063] S01. Screening the active material particles 12 into N types of active material particles 12 according to their sizes.

[0064] The size range of each type of active material particles 12 is x N ~y N , and 1 / 3y N <x N <y N ; N is an integer greater than or equal to 1.

[0065] S02. Manufacturing N types of pores 110 corresponding to the N type active material particles 12 on the solid electrolyte membrane.

[0066] The perimeter C of each type of hole 110 is N Satisfies: 1 / 3πy N <C N <πx N .

[0067] In some embodiments, after the active material particles 12 are sprayed on the porous solid electrolyte membrane 11 , the following steps are included: ultrasonicating and rearranging the active material particles 12 .

[0068] In some embodiments, after rolling, the following steps are included: recovering the active material particles 12 .

[0069] In some embodiments, the pole piece 1 of the present application is formed by Figure 3 The electrode sheet preparation device 2 shown is prepared, and the electrode sheet preparation device 2 includes a conveyor belt and a laser puncher 21, a main material powder sprinkler 22, and a roller pressing device 23 arranged on the conveyor belt in sequence. The laser puncher 21 is used to punch holes in the solid electrolyte membrane to form channels 110 on the porous solid electrolyte membrane 11. The main material powder sprinkler 22 is used to spray active material particles 12 on the porous solid electrolyte membrane 11. The roller pressing device 23 is used to press the active material particles 12 into the channels 110 of the porous solid electrolyte membrane 11, so that the active material particles 12 and the channels 110 of the porous solid electrolyte membrane 11 are interference fit.

[0070] In some embodiments, the preparation device 2 further includes an ultrasonic homogenizer 24 and an intercepting homogenizer 25, which are arranged on a conveyor belt between the main material duster 22 and the roller pressing device 23. The ultrasonic homogenizer 24 is used to ultrasonicate the active material particles 12, and the intercepting homogenizer 25 is used to rearrange the active material particles 12 so that the active material particles 12 enter the pores 110 as much as possible.

[0071] In some embodiments, the preparation device 2 further includes a micro-negative pressure powder absorber 26, which is disposed at the rear end of the roller pressing device 23 on the conveyor belt. The micro-negative pressure powder absorber 26 is used to recover the excess active material particles 12.

[0072] The third aspect of the present application provides a solid-state battery, which includes two pole pieces 1 provided in the first aspect or pole pieces 1 prepared by the preparation method provided in the second aspect and a dense solid electrolyte membrane. The active material particles 12 are positive electrode active material particles 12 or negative electrode active material particles 12, wherein one pole piece 1 is a positive electrode active material particle 12, and the other pole piece 1 is a negative electrode active material particle 12. The dense solid electrolyte membrane is arranged between the two pole pieces 1.

[0073] The solid-state battery provided in the present application has a porous solid electrolyte membrane 11 in the pole piece 1. The porous solid electrolyte membrane 11 has good compatibility with the dense solid electrolyte membrane, thereby reducing the interface impedance between the pole piece 1 and the dense solid electrolyte membrane.

[0074] In some embodiments, the material of the positive electrode active material particles 12 is one or more of lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide.

[0075] In some embodiments, the negative electrode active material particles 12 are made of one or more of graphite, silicon oxide, silicon carbon, and lithium metal.

[0076] Herein, the role of the "dense solid electrolyte membrane" is to act as a diaphragm to separate the positive and negative electrodes and avoid contact short circuit. To this end, the material of the dense solid electrolyte membrane may include a binder, a solid electrolyte and an electrolyte salt, but not a conductive agent. Since drilling is not required, the present application does not limit the type of solid electrolyte in the dense solid electrolyte membrane, which can be either an organic solid electrolyte or an inorganic solid electrolyte.

[0077] It can be understood that the two pole pieces 1 provided in the present application, which respectively contain positive electrode active material particles and negative electrode active material particles, and a dense solid electrolyte membrane can form a complete battery structure without the need for an additional composite current collector. Subsequently, aluminum strips or copper strips can be welded on the positive electrode piece or the negative electrode piece respectively to form a positive electrode ear or a negative electrode ear on the battery structure.

[0078] In some embodiments, the inorganic solid electrolyte is selected from one or more of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte.

[0079] In some embodiments, the oxide solid electrolyte includes at least one of garnet-type lithium lanthanum zirconium oxide (LLZO), NASICON type, and LISICON type.

[0080] NASICON type oxide solid electrolyte is AM′M″P3O 12The molecular formula is sodium superionic conductor, in which A is usually a monovalent transport cation, such as at least one alkali metal ion such as Na, K, Li, etc., and the positions of M' and M" can be either divalent or trivalent cations (such as Zn 2+ Mg 2+ 、Ni 2+ Cr 3+ 、Al 3+ Sc 3+ , Fe 3+ 、In 3+ and Y 3+ etc.), or a tetravalent or pentavalent cation (such as Ti 4+ 、Zr 4+ ,Ge 4+ Sn 4+ 、V 5+ , Nb 5+ 、As 5+ In addition, P 5+ It can also be replaced by other high-valent ions such as Si 4+ 、V 5+ , Nb 5+ For example, the NASICON type oxide solid electrolyte may be, but is not limited to, Na3Zr2Si2PO 12 .

[0081] LISICON oxide solid electrolyte is a lithium ion conductor, which contains a solid three-dimensional anion skeleton. The skeleton ions provide a transport channel for the transfer of lithium ions. + In the interstitial position, it can migrate and conduct electricity, and the interstitial lithium ions have good proton exchange ability. In the exemplary embodiment, the LISICON type oxide solid electrolyte can be but is not limited to Li 4-x Ge 1-x P x S4, wherein x may be 0.01-0.99. In an exemplary embodiment, the value of x may be 0.01, 0.05, 0.1, 0.5, 0.75, 0.9, 0.99, and other typical but non-limiting values.

[0082] In some embodiments, the sulfide solid electrolyte includes at least one of Li2S-P2S5, Li2S-SiS2, and Li2S-B2S3.

[0083] In some embodiments, the halide solid electrolyte includes LiaMY4, LiaMY6 and LiaMY8, wherein M may include at least one of metals Mn, Zn, Fe, Al, Yb, etc., and Y may include at least one of halogens F, Cl, Br, I.

[0084] A fourth aspect of the present application provides an electrical device, which includes the solid-state battery provided by the third aspect.

[0085] Solid-state batteries can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices may include, but are not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0086] The present application will be further described below with reference to specific embodiments and comparative examples.

[0087] Example 1

[0088] Positive electrode:

[0089] The material of the positive electrode active material particles used in this embodiment is lithium iron phosphate material. Among them, the maximum particle size d of the positive electrode active material particles is 正极 =5 μm±0.05 μm.

[0090] The solid electrolyte membrane includes organic solid electrolyte polyethylene oxide, conductive agent carbon nanotubes, binder polyvinylidene fluoride and lithium salt lithium bis(trifluoromethanesulfonyl imide) in a mass ratio of 5:3:1:3. The preparation steps are as follows:

[0091] (1) First, laser drilling is performed on the solid electrolyte membrane to form channels to obtain a porous solid electrolyte membrane.

[0092] Among them, the perimeter of the hole C 正极 is 10 μm, and the depth of the pore D 正极 is 5.5 μm; the center distance between two adjacent channels is L 正极 is 20 μm.

[0093] (2) Then, the positive electrode active material particles are sprayed onto the corresponding pore surface, firstly ultrasonicated and rearranged using an ultrasonic homogenizer and an intercepting homogenizer, and then rolled twice to obtain a positive electrode sheet.

[0094] Negative plate:

[0095] The material of the negative electrode active material particles used in this embodiment is graphite. The maximum particle size d 负极 =30 μm±0.3 μm.

[0096] The solid electrolyte membrane includes organic solid electrolyte polyethylene oxide, conductive agent carbon nanotube, binder polyvinylidene fluoride and lithium salt lithium bistrifluoromethanesulfonyl imide in a mass ratio of 5:1:1:3.

[0097] The preparation steps are as follows:

[0098] (1) First, laser drilling is performed on the solid electrolyte membrane to form channels to obtain a porous solid electrolyte membrane.

[0099] Among them, the perimeter of the hole C 负极 is 50 μm, and the depth of the pore D 负极 is 35 μm; the center distance between two adjacent channels is L 负极 is 100 μm.

[0100] (2) Then, the negative electrode active material particles are sprayed onto the corresponding pore surface, firstly ultrasonicated and rearranged using an ultrasonic homogenizer and an intercepting homogenizer, and then rolled twice to obtain a negative electrode sheet.

[0101] Solid-state batteries:

[0102] The positive electrode sheet, the negative electrode sheet and the dense solid electrolyte membrane are rolled together to prepare a solid-state battery.

[0103] Among them, the dense solid electrolyte membrane includes organic solid electrolyte polyethylene oxide, binder polyvinylidene fluoride and lithium salt lithium bis(trifluoromethanesulfonyl imide) in a mass ratio of 5:1:3.

[0104] Example 2

[0105] The preparation method of the positive electrode sheet, the negative electrode sheet and the solid-state battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0106] The circumference of the laser-punched hole in the porous solid electrolyte membrane in the positive electrode is C 正极 =5 μm;

[0107] The circumference of the hole in the porous solid electrolyte membrane in the negative electrode sheet is C 负极 =30 μm.

[0108] Example 3

[0109] The preparation method of the positive electrode sheet, the negative electrode sheet and the solid-state battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0110] The depth D of the laser-drilled pores in the porous solid electrolyte membrane in the positive electrode sheet 正极 5 μm;

[0111] Depth D of the laser-drilled pores in the porous solid electrolyte membrane in the negative electrode sheet 负极 is 30 μm.

[0112] Example 4

[0113] The preparation method of the positive electrode sheet, the negative electrode sheet and the solid-state battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0114] The center distance L between two adjacent channels of the laser-drilled porous solid electrolyte membrane in the positive electrode sheet 正极 5 μm;

[0115] The center distance L between two adjacent holes in the porous solid electrolyte membrane in the negative electrode sheet 负极 is 30 μm.

[0116] Example 5

[0117] The preparation method of the positive electrode sheet, the negative electrode sheet and the solid-state battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0118] The center distance L between two adjacent channels of the laser-drilled porous solid electrolyte membrane in the positive electrode sheet 正极 60 μm;

[0119] The center distance L between two adjacent holes in the porous solid electrolyte membrane in the negative electrode sheet 负极 is 320μm.

[0120] Comparative Example 1

[0121] Positive electrode:

[0122] 1) The organic solid electrolyte polyethylene oxide, the binder polyvinylidene fluoride, the conductive agent carbon nanotubes, the lithium salt lithium bis(trifluoromethanesulfonyl imide) and the pore-forming agent polymethyl methacrylate are mixed and rolled into a film, and then the pore-forming agent is removed under high-temperature calcination conditions to form a pore structure that is interconnected to obtain a porous solid electrolyte membrane.

[0123] Among them, the mass ratio of organic solid electrolyte polyethylene oxide, binder polyvinylidene fluoride, conductive agent carbon nanotube, lithium salt lithium bis(trifluoromethanesulfonyl imide) and pore-forming agent polymethyl methacrylate is 5:0.5:0.5:0.5:0.5.

[0124] 2) Filling the positive electrode active material particles into the porous solid electrolyte membrane, wherein the material of the positive electrode active material particles is lithium iron phosphate material.

[0125] Negative plate:

[0126] The porous solid electrolyte membrane is prepared in the same manner as the positive electrode sheet, and the negative electrode active material particles are filled into the porous solid electrolyte membrane, wherein the material of the negative electrode active material particles is graphite.

[0127] Solid-state batteries:

[0128] The positive electrode sheet, the negative electrode sheet and the dense solid electrolyte membrane are rolled together to prepare a solid-state battery.

[0129] Among them, the dense solid electrolyte membrane includes organic solid electrolyte polyethylene oxide, binder polyvinylidene fluoride and lithium salt lithium bis(trifluoromethanesulfonyl imide) in a mass ratio of 5:1:3.

[0130] Comparative Example 2

[0131] The preparation methods of the positive electrode sheet, the negative electrode sheet and the solid-state battery in this comparative example are basically the same as those in Example 1, except that:

[0132] The circumference of the laser-punched hole in the porous solid electrolyte membrane in the positive electrode is C 正极 =16 μm;

[0133] The circumference of the hole in the porous solid electrolyte membrane in the negative electrode sheet is C 负极 =100 μm.

[0134] Performance Testing

[0135] The solid-state batteries provided in the above embodiments and comparative examples were tested as follows:

[0136] (1) Impedance test

[0137] Adjust the battery SOC to 50% with 0.5C current, leave it for 2h, record the voltage U0, discharge it with 1.5C constant current for 30s, record the voltage U1; calculate DCR as: (U0-U1) / I (1.5C) The test results are shown in Table 1.

[0138] (2) Capacity test and cycle performance test

[0139] Charge at 0.5C current to the upper cut-off voltage; leave for 30 minutes; discharge at 0.5C current to the lower cut-off voltage; leave for 30 minutes; repeat the above steps for 200 cycles; record the capacity of the first cycle and the capacity of the 200th cycle; calculate the cycle capacity retention rate: (200th cycle capacity / 1st cycle capacity*100%). The test results are shown in Table 1.

[0140] Table 1

[0141]

[0142] As shown in Table 1, by comparing Examples 1 to 5 and Comparative Examples 1 to 2, it can be seen that the electrode provided by the present application reduces the impedance of the battery while improving the capacity performance of the battery and improving the cycle capacity retention rate of the battery.

[0143] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0144] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the technical concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A pole piece, characterized in that: include: The porous solid electrolyte membrane has a plurality of discrete pores, wherein active material particles are arranged in the pores, and at least part of the active material particles are interference fit with the pores.

2. The pole piece according to claim 1, characterized in that: The circumference C of the pore and the maximum particle size d of the active material particles satisfy: 1 / 3πd <C<πd。 3. The pole piece according to claim 1, characterized in that: The center distance L between two adjacent channels and the maximum particle size d of the active material particles satisfy: 1.1d <L<10d。 4. The pole piece according to claim 1, characterized in that: The depth D of the pores and the maximum particle size d of the active material particles satisfy the following condition: D>1.05d.

5. The pole piece according to any one of claims 1 to 4, characterized in that: The solid electrolyte in the porous solid electrolyte membrane is an organic solid electrolyte.

6. A method for preparing a pole piece, characterized in that: The following steps are involved: Spraying active material particles on the porous solid electrolyte membrane, and then rolling it so that at least part of the active material particles are interference-fitted with the pores of the porous solid electrolyte membrane; Wherein, the pores of the porous solid electrolyte membrane are arranged separately from each other.

7. The method for preparing a pole piece according to claim 6, characterized in that: The number of times of rolling is greater than or equal to twice.

8. The method for preparing a pole piece according to claim 6, characterized in that: Before the rolling, the following steps are also included: The active material particles are sonicated and rearranged.

9. A solid-state battery, characterized in that: include: Two pole pieces according to any one of claims 1 to 5 or pole pieces prepared by the preparation method according to any one of claims 6 to 8, wherein the active material particles are positive electrode active material particles or negative electrode active material particles, one pole piece is positive electrode active material particles, and the other pole piece is negative electrode active material particles; and The dense solid electrolyte membrane is arranged between the two pole pieces.

10. An electrical device, characterized in that: Comprising a solid-state battery as described in claim 9.